Retinitis Pigmentosa: over‐expression of anti‐ageing protein Klotho in degenerating photoreceptors. (22nd July 2013) - Farinelli, Pietro; Arango‐Gonzalez, Blanca; Völkl, Jakob; Alesutan, Ioana; Lang, Florian; Zrenner, Eberhart; Paquet‐Durand, François; Ekström, Per A.R.
Abstract Retinitis Pigmentosa involves a hereditary degeneration of photoreceptors by as yet unresolved mechanisms. The secretable protein α‐Klotho has a function related to ageing processes, and α‐Klotho‐deficient mice have reduced lifespan and declining functions in several tissues. Here, we studied Klotho in connection with inherited photoreceptor degeneration. Increased nuclear immunostaining for α‐Klotho protein was seen in degenerating photoreceptors in four different Retinitis Pigmentosa models (rd1, rd2 mice; P23H, S334ter rhodopsin mutant rats). Correspondingly, in rd1 retina α‐Klotho mRNA expression was significantly up‐regulated. Moreover, immunostaining for another Klotho family protein, β‐Klotho, also co‐localized with degenerating rd1 photoreceptors. The rd1 retina displayed reduced levels of fibroblast growth factor 15, a member of the fibroblast growth factor subfamily for which Klotho acts as a co‐receptor. Exogenous α‐Klotho protein added to retinal explant cultures did not affect cell death in rd1 retinae, but caused a severe layer disordering in wild‐type retinae. Our study suggests Klotho as a novel player in the retina, with a clear connection to photoreceptor cell death as well as with an influence on retinal organization.